(untitled) (Вісник: Міжнародні відносини, 2025)
Background. The outline and detailed analysis of the geopolitical positioning of Ukraine and Poland in the Baltic – Black Sea Region in the context of foreign policy identification of the states as regional leaders and key ‘poles’ of the geopolitical matrix of this space are important in the process of determining the degree of influence of these countries at the regional level, identifying the main points of intersection of their foreign policy interests and identities and determining their potential to establish bilateral and multilateral interactions at the current stage. Methods. In the preparation of the study, the authors used the following methods: systemic approach, comparative method, structural and functional method, world–system analysis. The geopolitical aspect of the methodology is represented by the geopolitical analysis of security problems through foreign policy and geography, as well as the methods of analysis and assessment of the geopolitical situation. Results. It was found that the geographical affiliation to the European subcontinent and the strategic importance of Ukraine’s foreign policy development for building a new configuration of not only regional, but also global systems of international relations have secured its status as the main driving force of transformations of the geopolitical situation in Europe. Considerable attention to the ‘Ukrainian issue’ in the context of Russia’s full-scale invasion of the territory of Ukraine contributes to the realization of Poland’s desire to establish its status of a geopolitical leader in the Baltic – Black Sea Region because Poland is one of the pioneers in providing assistance to the official Kyiv and acts as the latter’s ‘international advocate’. Since the Baltic – Black Sea Region should not fall under control of any extra-regional actor, while establishing further practical mutually beneficial cooperation, Ukraine and Poland may realize that their common interests in confronting geopolitical challenges allow them to strengthen the significance of their geopolitical leadership in the Baltic – Black Sea Region in the context of their foreign policy identification. Conclusions. Considering that Poland has acted as a transit territory for Western European influences in Ukraine for a long time, it is determined that close cooperation of the states as key ‘poles’ of the geopolitical matrix of the Baltic – Black Sea Region will ensure the stability of this geopolitical area by establishing its interconnections with the wider geopolitical spaces not only in Europe, but also in the world as a whole.